PERAN WORD OF MOUTH MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KULINER - Ningsih, Andria; Hurnis, Delfi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This research aims to test and analyze how the influence of word of mouth mediates social media marketing on purchasing decisions. The population that will be used as research is 100 people. The sampling technique in this research was carried out using a purposive sampling method. The design used in this research is based on survey research hypothesis testing method data. The types of data in this research are qualitative and quantitative data. The collected data will be analyzed descriptively and processed using PLS version 4.0. The results of the analysis show that Social Media Marketing significantly strengthens the influence on Purchasing Decisions, Word of Mouth significantly strengthens the influence on Purchasing Decisions. And Word of Mouth significantly weakens the negative influence of Social Media Marketing on Purchasing Decisions.